2007
DOI: 10.1097/cmr.0b013e3282f1d328
|View full text |Cite
|
Sign up to set email alerts
|

The p.G23S CDKN2A founder mutation in high-risk melanoma families from Central Italy

Abstract: We have investigated the frequency and spectrum of CDKN2A/CDK4 mutations in 23 cutaneous melanoma families from Central Italy (Tuscany). Three distinct mutations were identified in five families. One mutation, p.G23S, was present in three families. Several lines of evidence indicate that p.G23S is a pathogenic mutation: it is located in the functionally important first ankyrinic domain of p16, it was not detected in a sample of 100 control individuals, and it was present in all tested affected individuals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…41,[51][52][53] Founder mutations are common among hereditary melanoma cases in some Italian regions, but this high prevalence in a defined area can not imply a national predictive value. 15,17,43,51,54 In the view of the implementation of next generation sequencing methods, eg, gene panels, in clinical genetic testing, further population studies are needed to establish the mutation prevalence and penetrance of these genes in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…41,[51][52][53] Founder mutations are common among hereditary melanoma cases in some Italian regions, but this high prevalence in a defined area can not imply a national predictive value. 15,17,43,51,54 In the view of the implementation of next generation sequencing methods, eg, gene panels, in clinical genetic testing, further population studies are needed to establish the mutation prevalence and penetrance of these genes in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, studies on smaller samples of families 9,[11][12][13][14][15] reported that CDKN2A mutations are found in Italian families with just two cases and in families with larger numbers of affected members.…”
mentioning
confidence: 99%
“…Most CDKN2A mutations are missense mutations located in the coding sequences of exons 1a and 2, and many seem to derive from ancestral founders. [2][3][4][5][6][7][8][9][10][11] CDKN2A mutations have been found in 20% to 40% of melanoma families with 3 or more affected members. 1 However, the proportion of families with mutations varies between countries, depending on factors such as baseline melanoma incidence rates and family and population selection in studies.…”
mentioning
confidence: 99%
“…Interestingly, the E27X is the first stop codon CDKN2A founder mutation detected in melanoma families presenting also PC and neuroblastoma, while PC was preferentially reported in association with exon 2 mutations, impairing both p16 and p14. In a study addressing the frequency and spectrum of CDKN2A/CDK4 mutations in families from central Italy, a third Italian founder mutation, the Gly23Ser (G23S), was detected (Gensini et al, 2007). Again, the haplotype analysis revealed a single common origin for the G23S and several lines of evidence (co-segregation with the disease and case-control studies) suggested its pathogenicity and its involvement in melanoma predisposition.…”
Section: Founder Mutationsmentioning
confidence: 99%
“…This study estimated a CDKN2A mutation rate of 33% overall, but single studies on families from different Italian regions reported variable mutation frequencies, with high values (>35%) for Liguria (Ghiorzo et al, 1999;Mantelli et al, 2002) and low values (7.3%) for Emilia Romagna and Marche (Landi et al, 2004). Moreover, the mutation frequency in melanoma families is approximately 17-22% for Lazio and Toscana in Central Italy (Binni et al, 2010;Gensini et al, 2007). Importantly, the frequency was found to be higher in regions with founder mutations (i.e.…”
Section: Mutational Analysis Of Melanoma-predisposing Genes In Italymentioning
confidence: 99%